Has European Integration Reached the End of the Road? - Tsoukalis, Loukas (Revista Análisis Internacional (Cesada a partir de 2015), 2015)
It is a great honour to be invited to give the Cyril Foster Lecture for 2014, and I should like to thank the Managers of the Cyril Foster Fund, Louise Fawcett in particular as Chair of the Committee, for the invitation.